A SYSTEMATIC LITERATURE REVIEW OF CULTURALLY-INFORMED INTERFACE DESIGN ON VISUAL ATTENTION AND RESPONSE TIME FROM EYE-TRACKING IN NEUROCOGNITIVE STUDIES - Anne Gracia; Gerard Anthonius Juswanto; Maria Caroline Wojtila; Rivo Panji Yudha; Sandra Yap Donggorables; Leni Aswati Novita Dewi; Basuki Pahala (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Purpose: This systematic literature review synthesizes empirical evidence regarding the effects of culturally-informed interface design on visual attention patterns and response times as measured through eye-tracking methodologies in neurocognitive studies. The study aims to identify research patterns, methodological approaches, and geographic representation in this rapidly evolving interdisciplinary field. Methods: Following PRISMA guidelines, a comprehensive search was conducted across five major academic databases (Scopus, Web of Science, PsycINFO, IEEE Xplore, ACM Digital Library) covering publications from 2010-2025. Search strategies combined terms related to cultural factors, interface design, and eye-tracking methodologies. Studies were systematically screened using predefined inclusion criteria, with data extraction focusing on study characteristics, methodological approaches, cultural contexts, and key findings. Results: From 390 initially identified studies, 116 (29.7%) met inclusion criteria for detailed analysis. The temporal distribution revealed exponential growth, with 46.7% of studies published during 2020-2025, peaking at 41 studies in 2024. Thematic analysis identified interface design (70.2%) and eye-tracking methodologies (59.3%) as dominant research foci, while cultural factors appeared in 50.5% of studies. Geographic analysis revealed significant imbalance, with Western cultures examined in 34 studies versus 11 studies focusing on Asian cultures. Methodological approaches showed limited adoption of experimental designs (5.7%) and virtual absence of neuroscience approaches (0.3%). Conclusions: The field has evolved from exploratory investigations to substantive scientific inquiry but requires strategic advancement in three critical areas: geographic and cultural diversity through expanded non-Western research, methodological sophistication through increased experimental rigor and neuroscience integration, and theoretical development through systematic framework integration. These findings provide evidence-based recommendations for developing inclusive design guidelines and establishing international collaborative research programs.